1981
DOI: 10.1128/jvi.39.2.559-572.1981
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 HindIII fragment L encodes spliced and complementary mRNA species

Abstract: We have used DNA bound to cellulose to isolate and translate in vitro herpes simplex virus type 1 (HSV-1) mRNA's encoded by HindIII fragment L (mapping between 0.592 and 0.647), an 8,450-base-pair (8.45-kb) portion of the long unique region of the viral genome. Readily detectable, late mRNA's 2.7 and 1.9 kb in size encoding 69,000-and 58,000-dalton polypeptides, respectively, were isolated. A very minor late mRNA family composed of two colinear forms, one 2.6 kb and one 2.8 kb, was isolated and found to encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 64 publications
10
63
0
Order By: Relevance
“…This probe detected only a single major mRNA species of approximately 1.8 kilobases in infected cells at all times examined ( Fig. 5), in agreement with the previously reported size of the transcript of this gene (7). The 65KDBP mRNA was first detected at 4 h p.i.…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…This probe detected only a single major mRNA species of approximately 1.8 kilobases in infected cells at all times examined ( Fig. 5), in agreement with the previously reported size of the transcript of this gene (7). The 65KDBP mRNA was first detected at 4 h p.i.…”
Section: Methodssupporting
confidence: 91%
“…The studies described in this report clearly demonstrate that the gene encoding 65KDBP is a member of the early or P kinetic class of HSV-1 genes as assessed by a number of parameters. Frink et al (7) initially classified the transcript from this gene as a ,B transcript on the basis of the presence of the transcript when DNA synthesis was inhibited with adenosine arabinoside. The pattern of protein accumulation that we found was consistent with the gene belonging either to the P or ,3y class.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the sequence which codes for gC-2, both of the other reading frames on that strand are closed, one with 14 termination codons, and the other with 4. Mapping of HSV-1 RNAs from this region has suggested that spliced RNAs may be present (11); however, additional RNAs or translation products have not been clearly demonstrated in this region of HSV-2. The mRNA which specifies the 18K protein uses a different reading frame from that of gC-2.…”
Section: Resultsmentioning
confidence: 98%